Peningkatan Kualitas Kemasan Tempe Menggunakan Mesin Continuous Sealer - Vita Pramaningsih; Marjan Wahyuni; Sayekti Harits Suryawan (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
Tempe is a cheap food that people widely consume at any level. In the Industrial Revolution 4.0, Small and Medium Industries (IKM in Indonesia, including tempe industries, were required to increase their productivity. Currently, the tempe packaging processes use manually by wax. It takes a long time, and there are problems while exposed to the wind; the candle will die. This activity aims to improve the tempe packaging process from manual to machine. Methode was used production location survey, interview about packaging process, purchasing and handover machine to the partner, and evaluating the packaging process using the device then describing it. The location of the activity was carried out in a household scale tempe industry, Gang Baru 2, Gunung Lingai, Samarinda, East Kalimantan. The result of the action was an increase in production; the packaging process was more efficient, and there were no obstacles. Tempe packaging becomes tidier and more attractive.